A NEW LOOK AT THE STUDY OF JOURNALISTIC TEXT IN LINGUISTICS (Scientific journal of the Fergana State University, 2024)
This article discusses textual studies and provides information on the development of the field of textual linguistics, which deals with textual studies. It was noted that significant work has been done in this direction in world linguistics. Today in modern linguistics the approach to journalistic language and its research has reached a new level.